Temporal and Spatial Variations of Secchi Depth and Di use Attenuation Coe cient from Sentinel-2 MSI over a Large Reservoir - Rodrigues, Gonçalo (2020)
The Alqueva reservoir (South of Portugal) in the Guadiana river basin constitutes the most important water resource in southern Portugal for domestic and agricultural consumption. We present a methodology developed to characterize spatial and temporal variations of Secchi depth and di use attenuation coe cient (both related to dissolved/suspended particles and to water transparency), using high spatial resolution satellite images from Sentinel-2 Multi-Spectral Instrument (MSI). Empirical relations between satellite retrievals of surface reflectances and in situ measurements of water parameters were defined and applied to the entire reservoir for spatial and temporal analysis in the period July 2017–June 2019, useful in the identification of microalgae blooms and rapid variations in water characteristics, which allowed us to di erentiate five zones. Water estimates with lower transparency and higher attenuation of radiation were found in the northern area of Alqueva reservoir during the months characterized by higher water temperatures, with Secchi depth monthly averages near 1.0 m and di use attenuation coe cient near or above 1.5 m 1. Satellite retrievals of water with greater transparency in the reservoir were obtained in the southern area in months with low water temperature and atmospheric stability, presenting some monthly Secchi depth averages above 3 m, and di use attenuation coe cient below 0.8 m 1. January 2018 presented great transparency of water with a Secchi depth of 7.5 m for pixels representing the 95th percentile and di use attenuation coe cient of 0.36 m for pixels representing the 5th percentile in the Southern region.